Marriage Requirements for Cadres of Pondok Pesantren Gontor: Exploring the Concept of Kafa’ah - Zulham Wahyudani; Muhazir Muhazir (Universitas Islam Sultan Agung, 2023)
This study aims to analyze the marriage requirements for cadres of Pondok Pesantren Gontor. Each cadre who wishes to marry must choose their own partner and obtain approval from the pesantren's leadership. If the leaders, including the kyai, does not grant approval, the cadre is not permitted to marry the chosen partner. In the tradition of Pondok Pesantren Gontor, approval from the pesantren's leaders is crucial to receiving blessings in the marriage. Such a practice has been in place for many years to maintain the pesantren's existence. This study seeks to analyze these unique marriage conditions for Gontor cadres and how these requirements are viewed from the perspective of kafa'ah. This research is empirical and uses a qualitative approach. Data was collected through interviews with the cadres and teachers at Pondok Pesantren Gontor, as well as an analysis of the pesantren's website. The concept of kafa'ah was derived from several sources of literature. The study finds that a potential wife must agree to adhere to the conditions applicable to cadres throughout their lives, including obedience to the pesantren's leaders, being ready to work at the pesantren 24 hours if needed, and being prepared to be assigned anywhere according to the pesantren leaders's orders. The concept of kafa'ah in this context can be justified as the alignment of the potential wife’s vision and mission with those of her husband (a Gontor cadre). This concept of kafa'ah differs from the textual understanding found in traditional fiqh texts and the Compilation of Islamic Law (KHI). This alignment is seen as essential for achieving welfare and as a form of self-dedication at Pondok Pesantren Gontor in Ponorogo, East Java, although this concept differs from the textual interpretation found in fiqh texts and the KHI.